Kepemimpinan Bu Nyai Sebagai Representasi Kesetaraan Gender dalam Tradisi Pondok Pesantren Al-Azhar Azzayyadiyah Sampang - Nur Hayati; Mohammad Muchlis Solichin; Ali Nurhadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This article examines the leadership of Bu Nyai at Al-Azhar Azzayadiyah Islamic Boarding School as a representation of gender equality within traditional Islamic educational institutions. This study employs a descriptive qualitative approach using in-depth interviews, participatory observation, and documentation studies as data collection techniques. The research focuses on how Bu Nyai exercises leadership authority within a pesantren environment that has long been influenced by patriarchal values. The findings reveal that Bu Nyai’s leadership is not only cultural and spiritual in nature, but also reflects the transformation of women’s roles within Islamic boarding schools. In carrying out her leadership, Bu Nyai applies charismatic, transformational, and value-based leadership styles grounded in Islamic teachings on justice and equality. This leadership is reflected in her ability to guide students, manage educational activities, build harmonious social relationships, and motivate members of the pesantren community. Furthermore, the presence of Bu Nyai as a leader demonstrates that women possess equal capabilities in developing Islamic educational institutions. The findings of this study provide important contributions to the development of gender studies in Islamic education in Indonesia, particularly regarding the strategic role of women in pesantren leadership.